Aging and liver disease. Issue 3 (May 2015) - Kim, In Hee; Kisseleva, Tatiana; Brenner, David A.
<x xml:space="preserve">Abstract</x> Purpose of review Aging is a condition in which a person gradually loses the ability to maintain homeostasis, due to structural alteration or dysfunction. Aging is a major risk factor for most chronic diseases. As the liver has a remarkable ability to regenerate, this review assessed the effect of aging on clinical liver disease with references to preclinical models when relevant to pathogenesis. Recent findings Aging has been shown to not only enhance vulnerability to acute liver injury but also increase susceptibility of the fibrotic response. Aging is associated with the severity and poor prognosis of various liver diseases including nonalcoholic fatty liver disease, alcoholic liver disease, hepatitis C, and liver transplantation. Summary Treatment of older patients with liver disease may require different or longer interventions. Transplantation of an older liver will be less tolerant of subsequent injury. Future studies are needed to understand more about the molecular mechanism of aging and contribute to the development of a noble treatment strategy that can block the progression of aging-induced liver diseases.